Towards a standard ammonite zonation for the Aptian (Lower Cretaceous) of northern Mexico - Ricardo Barragán-Manzo; Ana Laura Méndez-Franco (Revista Mexicana de Ciencias Geológicas)
Detailed data on twenty-seven species of ammonites identiﬁed in three stratigraphic sections of northern Mexico, allow further reﬁnement of the Aptian ammonite biozonations of previous authors. Four formal ammonite biozones are proposed. Dufrenoyia justinae Taxon-Range-Zone for the uppermost part of the lower Aptian (Bedoulian), Epicheloniceras cf. subnodosocostatum/Acanthohoplites acutecosta Interval Zone representative of the middle Aptian (Gargasian), and Acanthohoplites aschiltaensis and Hypacanthoplites cf. leanzae Taxon-Range-Zones, spanning the upper Aptian (Clansayesian). The ammonite zonation proposed represents the advancements on the development of a standard scheme towards a reliable correlation with the biozonal scheme of England and the ammonite zonal standard of the Mediterranean area.